A Defensoria Pública da União e a tutela coletiva dos Direitos Sociais - Queiroz, Taísa Bittencourt Leal (2013)
This study aims to analyze the role of the Defensoria Pública da União ( DPU ) as an instrument to collectively put into practice the social rights prescribed by the Brazilian Constitution. First, this study will analyze the historical and normative aspects of the creation and regulation of the institution in the Constitution and infra-constitutional laws. In addition, this study will discuss its organizational structure and the spheres of action of the Federal Public Defender. Next, this study will passes to the study of collective protection of social rights, starting it with a brief historical analysis of the development of standards defining social rights in the Brazilian constitucionalism, followed by the verification of the need of adoption these rights and later analysis of jurisprudence of the Supreme Court regarding the state inaction in enforcing these rights in the past five years. After, this study will analyze aspects of constitutional and infra-constitutional processualistic for strengthening social rights under the collective perspective, commenting the main procedural instruments, as well as the controversies regarding the role of the Defensoria Pública as a mechanism of collective protection of the social rights, discussing the existing conflict regarding the actual legal authority to prosecute class actions and the issue of the limited effectiveness of res judicata in public class actions. Finally, we analyze specific cases in which the role of the Defensoria Pública da União contributed to the process of making effective certain constitutional provisions.